Analysis of Outgoing General Cargo Handling at PT Angkasa Pura Logistik Semarang - Putri Fadhila Ardiansyah; Fathima Azzahra (Asian Journal of Logistics Management, 2025)
The global growth of e-commerce has accelerated demand for fast and efficient air freight services, positioning general cargo as a critical component of modern logistics systems. However, the increasing volume of shipments frequently generates operational challenges, most notably shipment delays, which ultimately undermine service quality and distribution efficiency. This study was conducted to analyse the general cargo outgoing handling process at PT Angkasa Pura Logistik, Semarang Branch, and to identify the key inhibiting factors encountered in its execution. A descriptive qualitative methodology was employed, with data gathered through direct observation, semi-structured interviews, and documentation review. Findings reveal that the primary constraints comprise workforce shortages, documentary discrepancies in shipping documents, and a structural imbalance between cargo volume and handling capacity. On the basis of these findings, an integrated action plan was developed, clearly delineating responsibility for addressing each root cause. The implementation of this action plan is expected to enhance operational efficiency, reduce service turnaround time, and strengthen inter-unit coordination. These findings are of significant strategic value as a reference for the continuous improvement of air cargo service quality.